Identification of association between rs1057317 polymorphism in TLR4 3′‐untranslated region and the susceptibility to osteoporosis. Issue 8 (15th April 2019) - Hong, Ronghua; Xie, Jingjing; Zhang, Fuguo; Pan, Hansong; Guo, Changjun
Abstract: It has been proved that the expression of TLR4 is associated with a reduced risk of osteoporosis (OP). One single‐nucleotide polymorphism located within the 3′‐untranslated region (3′‐UTR) of TLR4 may "generate" binding site of miR‐34a and thereby associated with risk of OP. Bioinformatics analysis and luciferase reporter assay were used to specify the effect of polymorphisms on the interaction between miR‐34a and TLR4 gene. Western blot analysis and real‐time polymerase chain reaction were used to study the expressions of miR‐34a, TLR4 in different groups or cells transfected with miR‐34a mimics or inhibitor. 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay was used to estimate the effect of miR‐34a on the apoptosis of osteoblast. TLR4 was identified as a target of miR‐34a, with negative regulatory relationship predicted. The expression levels of miR‐34a was comparable with each other between CC, CA, and AA groups, and the expression levels of TLR4 was evidently lower in CC compared with GG and GC groups. Also, TLR4 level in culture osteoblast (genotyped as CC) treated with miR‐34a mimics was substantially downregulated compared with scramble control, while those cells (genotyped as CC) treated with miR‐34a inhibitors showed increased expression of TLR4. Additionally, the apoptosis of osteoblast genotyped as CC was decreased following transfection with miR‐34a mimics, while evidently promoted subsequent to transfect with miR‐34a inhibitor. The regulatory association between rs1057317 polymorphism in TLR4 3′‐UTR led to an inhibitory effect on the expression of TLR4 by miR‐34a, which may explain the observed association between the polymorphism and the susceptibility to OP. Abstract : It has been proved that the expression of TLR4 is associated with a reduced the risk of osteoporosis (OP). One single‐nucleotide polymorphism (SNP) located within the 3′‐untranslated region (3′‐UTR) of TLR4 may "generate" binding site of miR‐34a and thereby associated with risk of OP. In this study, we verified the regulatory association between rs1057317 polymorphism in TLR4 3′‐UTR led to an inhibitory effect on expression of TLR4 by miR‐34a, which may explain the observed association between the polymorphism and the susceptibility to OP.